2010
DOI: 10.1021/pr100044d
|View full text |Cite
|
Sign up to set email alerts
|

Increased Apoptosis after Autoimmune Regulator Expression in Epithelial Cells Revealed by a Combined Quantitative Proteomics Approach

Abstract: Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive autoimmune disease, affecting many endocrine tissues. APECED is associated to the lack of function of a single gene called AutoImmune REgulator (AIRE). Aire knockout mice develop various autoimmune disorders affecting different organs, indicating that Aire is a key gene in the control of organ-specific autoimmune diseases. AIRE is mainly expressed by medullary thymic epithelial cells (mTECs), and its absence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
(84 reference statements)
0
23
0
Order By: Relevance
“…10 Accordingly, loss of AIRE was observed in both human and murine thymomas. 23,24 Other studies indicated a role of AIRE in increasing apoptosis when expressed in thymic and thyroid epithelial models [8][9] , suggesting that overproduction of TSAs rather than induction of an apoptotic program might indirectly induce cellular stress leading to death. Such a role does not conflict with the nature of AIRE as a transcription factor, since it favors a continuous turnover of antigen-presenting mTECs and promote cross-presentation of tissue-specific antigens to developing thymocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Accordingly, loss of AIRE was observed in both human and murine thymomas. 23,24 Other studies indicated a role of AIRE in increasing apoptosis when expressed in thymic and thyroid epithelial models [8][9] , suggesting that overproduction of TSAs rather than induction of an apoptotic program might indirectly induce cellular stress leading to death. Such a role does not conflict with the nature of AIRE as a transcription factor, since it favors a continuous turnover of antigen-presenting mTECs and promote cross-presentation of tissue-specific antigens to developing thymocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Since individual mTECs transcribe TSA genes stochastically to favor a continuous turnover of presented antigen peptides, AIRE supports mTEC apoptosis. [8][9][10] Moreover, AIRE acts in the tolerance process by favoring the development of regulatory T cells. 11,12 Not only is AIRE highly expressed in mTECs, but there is evidence of AIRE expression in murine peripheral lymphoid organs.…”
Section: Introductionmentioning
confidence: 99%
“…Our data also showed an up-regulation of a number of chaperones (Hspe1, Hspa1a, and Hspb1). In the study carried out by Colome et al (27), 2D difference gel electrophoresis (DIGE) and Isotope coded pro- tein labeling (ICPL) were used to analyze the effect of AIRE on the cellular proteome of the AIRE-transfected and nontransfected epithelial cell line. They showed a similar increase in the levels of several chaperones (HSC70, HSP27, and tubulinspecific chaperone A) in AIRE-expressing cells, while various cytoskeleton-interacting proteins (transgelin, caldesmon, tropomyosin alpha-1 chain, myosin regulatory light polypeptide 9, and myosin-9) were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…They showed a similar increase in the levels of several chaperones (HSC70, HSP27, and tubulinspecific chaperone A) in AIRE-expressing cells, while various cytoskeleton-interacting proteins (transgelin, caldesmon, tropomyosin alpha-1 chain, myosin regulatory light polypeptide 9, and myosin-9) were decreased. We could identify at least five proteins in our proteomics data (heat shock protein beta 1 (Hspb1), Post synaptic density protein (PSD95), Drosophila disc large tumor suppressor (Dlg1), and zonula occludens-1 protein (zo-1) (PDZ) and Lin11, Isl-1 & Mec-3 (LIM) domain protein, trp/asp (WD) repeat containing protein 1, tubulinspecific chaperone A, and keratin type I cytoskeletal 18) that were shown to be modulated in the study carried out by Colome et al (27). Their studies suggest that AIRE-positive cells were more likely to undergo spontaneous apoptosis and that they were less resistant to apoptosis inducers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation